IMPLEMENTASI PROGRAM WOMENPRENEURSHIP DALAM PEMBERDAYAAN KELOMPOK WANITA TANI SRI REJEKI II DESA LINGGAPURA, KECAMATAN TONJONG, BREBES - Prasetyo, Kunandar; Utami, Dewanti Risa; Wicaksari, Sifa Aulia; Prasetya, Emanuel Desta Herry; Prabawa, Ilham Agung (Jurnal Abdi Insani, 2025)
Women Farmer Groups (KWT) represent one form of women's institutional organization that plays a crucial role in community empowerment. KWT Sri Rejeki II was established as an effort to enhance women's participation in the agricultural sector, particularly in post-harvest activities, processing, and marketing of agricultural products, thereby contributing directly to improving household welfare through income source diversification. Various challenges are faced by the group, including aspects of production, management, and product marketing. The community service activities conducted were designed through a structured approach by implementing four stages of activities: preparation, implementation, mentoring and evaluation, and sustainability phases. During the implementation stage, activities carried out included institutional training for KWT, Good Manufacturing Practices (GMP) training, product packaging training, photography and promotional media development training, and digital marketing training. The community service activities that have been conducted successfully enhanced the knowledge and skills of group members in business development, particularly in institutional aspects, good food production practices, marketing, and business management aspects.